“STUDY OF STRUCTURAL PARAMETERS AND CATION DISTRIBUTION OF CU2+ IONS SUBSTITUTED NICKEL FERRITES” - KAVADE, R.B.; VIDHATE, R.G.; BHANDARI, J. M.; SHUKLA, S.J. (Innovare Journal of Sciences, 2020)
Objective: To prepare and study the Cu2+ion substituted nickel ferrites with reference to structural parameters and cation distribution Materials and Methods: The samples of Cu2+ substituted nickel ferrites having the composition formula Ni1-XCuXFe2O4 (x = 0.0, 0.4, 0.8.) were prepared by solid state reaction technique using AR grade oxides. The formation of mono phase cubic spinel structure of all the samples under investigation have been carried out using XRD technique at room temperature. X-ray diffraction data were used to calculate structural parameters and X-ray intensity ratios were calculated for selected planes (220), (400), (440) and compared with the observed intensity ratios in order to obtain cation distribution. Results: The results of the cation distribution indicate that Cu2+ and Fe3+ occupy both sites whereas Ni2+ occupy octahedral B site. In this work we report our results on structural parameters and cation distribution of mixed Ni-Cu spinel ferrites. Conclusion: The structural parameters of nickel-copper system increases with Copper ions.